DESIGNING NUTRITION NEED ANALYSIS COUNTER SOFTWARE - Titin Hera Widi Handayani (Directorate of Research and Community Services, Universitas Negeri Yogyakarta, 2016)
This study was aimed at designing software that can calculate the nutritional needs of the community. The device is generated from an application program that is speciﬁ cally designed to determine lean body mass, nutritional status and nutritional value needs. It is guided by the science of nutrition and health in an efﬁ cient, inexpensive and accurate ways. This study used design software method. The ﬁ rst stage of the analysis, which consists of user needs analysis, job analysis, and technology analysis. The second stage is a block diagram including interface design and ﬂ owchart design. The third stage, design modules translation was done using a programming language into the application form called coding/ implementation. The fourth stage was testing the system using black box testing. The application design includes the creation of database structure, program ﬂ ow design and user interface. The design of the database was realized in 9 tables. The ﬂ ow program was depicted in Entity Relationship Diagram, Data Flowchart and Applications Flowchart. The interface design consisted of 17 display interface/ application form.